2021
DOI: 10.1111/ced.14567
|View full text |Cite
|
Sign up to set email alerts
|

Janus kinase inhibitors for atopic dermatitis: a promising treatment modality

Abstract: Summary Atopic dermatitis (AD) is chronic, pruritic, inflammatory skin disease that affects a significant portion of the population in industrialized nations. For nonresponders to conventional therapies, AD can significantly reduce sleep quality and quality of life. AD pathogenesis is multifactorial and involves multiple immune pathways, with recent evidence of T helper (Th)2, Th17 and Th22 axis attenuation in various AD endotypes and racial subtypes. Inhibition of the conserved Janus kinase (JAK) signalling p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 32 publications
1
38
0
Order By: Relevance
“…Oral formulations include abrocitinib, upadacitinib, baricitinib, and gusacitinib, and are suitable to treat moderate-to-severe AD. Topical formulations include ruloxitinib, beprocitinib, and delgocitinib [77].…”
Section: Atopic Dermatitismentioning
confidence: 99%
“…Oral formulations include abrocitinib, upadacitinib, baricitinib, and gusacitinib, and are suitable to treat moderate-to-severe AD. Topical formulations include ruloxitinib, beprocitinib, and delgocitinib [77].…”
Section: Atopic Dermatitismentioning
confidence: 99%
“…Thus, the dual inhibition of JAK and SYK can widen the range of targeted cytokines and increase the clinical efficacy of JAK inhibition by resolving different subtypes of AD. Clinical trials with gusacitinib have indicated good tolerability and significant reduction in pruritus and inflammatory lesion count [199,200].…”
Section: Emerging Therapeutic Small Molecules For Admentioning
confidence: 99%
“…A novel frontier in the treatment of AD is represented by JAK-inhibitors, small molecules that can be used both in the topical formulation thanks to their low molecular weight (about 300 kDa lower than the skin barrier threshold), and in the systemic oral formulation [ 119 , 120 ]. These include delgocitinib, ruxolitinib, and tofacitinib as topic formulations, baricitinib, upadacitinib, abrocitinib, and gusacitinib as systemic drugs [ 121 , 122 ]. Delgocitinib (pan-JAK-inhibitor) in ointment formulation improved clinical signs and symptoms in children and in adults with AD and it was well tolerated [ 123 , 124 , 125 ].…”
Section: Therapeutic Approach To Atopic Dermatitismentioning
confidence: 99%